The Effect of Corporate Social Responsibility, Company Size, Profitability on Tax Management in the Healthcare Sector Listed on the Indonesia Stock Exchange - Novanto, Yosan; Bwarleling, Theresia Hesti (Jurnal Sains Sosio Humaniora, 2026)
Tax management has become an important issue for companies in maintaining financial performance while fulfilling their tax obligations. This study aims to analyze the effects of Corporate Social Responsibility (CSR), Firm Size, and Profitability (Return on Assets/ROA) on Tax Management in healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employed a quantitative approach with a causal-comparative design and utilized secondary data obtained from annual reports and sustainability reports. The population consisted of 36 healthcare companies, while the sample was selected using a purposive sampling method, resulting in nine companies that met the specified criteria over a four-year observation period. The data were analyzed using panel data multiple regression analysis, supported by model selection tests, classical assumption tests, hypothesis testing, and coefficient of determination analysis. The findings reveal that Corporate Social Responsibility (CSR) does not have a significant effect on Tax Management. In contrast, Firm Size and Profitability (ROA) have a positive and significant effect on Tax Management. Furthermore, the coefficient of determination (R²) indicates that CSR, Firm Size, and Profitability explain 31% of the variation in Tax Management, while the remaining 69% is influenced by other factors not examined in this study. These findings suggest that company characteristics, particularly firm size and profitability, play a more substantial role in influencing tax management practices than CSR activities in healthcare companies.